Thoracoscopic treatment of a rare bilateral extralobar lung sequestration in a 3-years old girl - Cosimo Bleve; Maria Luisa Conighi; Diego Biondini; Pier Luca Ceccarelli; Leonardo Giarraputo; Sergio Savastano; Salvatore Fabio Chiarenza (PAGEPress Publications, 2021)
Majority of sequestrations fall into two categories: Intra-Lobar (ILS) and Extra-Lobar (ELS). Rarely the abnormal lung could be attached to the gastrointestinal tract, Bronchopulmonary Foregut Malformation (BPFM). We described a case of a girl of 3-years-old with antenatal diagnosis of left intrathoracic mass of the inferior lobe. Postnatal Computed-Tomography (CT) revealed a bilateral ELS with an isthmic bridge crossing the vertebral spine. She follows a MRI follow-up at 18months/30months confirming the lesion. Before surgery, a three-dimensional-CT-angiography was performed to study the mass, its blood supply and to plan surgery. She underwent to thoracoscopic resection. Two aberrant blood vessels were dissected from the thoracic aorta and ligated. The postoperative course was uneventful. She was discharged after 3 days. The rarity of our case is due to the bilateral extension. An appropriate preoperatory imaging study is necessary for the success of surgery while thoracoscopy is particularly appropriate in surgical treatment.